(untitled) (Journal of Asian Development Studies, 2024)
The principle of Common but Differentiated Responsibilities (CBDR) was meant to balance fairness and action by recognizing historical emissions and differing capabilities. However, it has become a two-sided weapon that seeks equality but hampers it simultaneously. The developed world advocates for equitable responsibility as emission levels increase globally, while the developing world seeks justice for previous transgressions. As such, CBDR has become both a mechanism for equitable distribution and a hindrance to much-needed action. The article’s results show that the CBDR principle has evolved into a political and legal conflict source, undermining effective climate change responses. The shift from binding emission reductions to voluntary Nationally Determined Contributions (NDCs) in the Paris Agreement is highlighted as a key concern, as it raises doubts about CBDR’s ability to address historical emissions disparities. The article also addresses how multinational corporations, as major contributors to emissions, are becoming an urgent focus in applying CBDR to non-state actors. It reveals how CBDR has led to political divisions, particularly between developed and developing nations, with the Global South calling for climate justice. Through cases like Urgenda Foundation v. Netherlands, the article highlights CBDR’s limitations in forcing non-compliant governments to take action on their climate responsibilities. Lastly, the article critiques the Paris Agreement’s reliance on voluntary NDCs, arguing that it weakens CBDR by allowing developed countries to set minimal emission reduction targets. As the climate crisis accelerates, the world must ask: Is CBDR still the magic bullet for fostering international cooperation, or is it the elephant in the room stalling the necessary solidarity needed to confront the threat of extinction?